Modul pendidikan STEM: Dispenser sanitasi tangan bebas sentuhan - Mohd Nasir, Mohd Hamzah; Zulkifli, Mohd Zamani; Bahari, Iskandar; Zainol Abidin, Mohd Roslan (2020)
An integrated module for STEM education with the model of development of a touchless hand sanitizer dispenser. It consists of 5 main modules including; (1) function design, (2) product and structure design (3) 3D modelling and printing (4) Arduino coding and electronic diagram, (5) Structure assembly. The module designed for the age between 12 and 17 years old.